Bicornuate uterus with recurrent pregnancy losses and bilateral tubal blockage managed with open metroplasty procedure: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Mullerian developmental anomalies (MDAs) adversely affect pregnancy outcomes. These anomalies are frequently associated with renal and axial skeleton abnormalities.Case presentation: A 33-year-old Para 0+3 was admitted to the gynecology ward with a history of three spontaneous abortions and secondary infertility for two years. She was sonographically diagnosed with a bicornuate uterus in 2016 as part of her workup for recurrent pregnancy losses. A repeat abdominal pelvic ultrasound done showed a bicornuate uterus and a right ectopic kidney. As a result, she was scheduled for hysteroscopy and laparoscopy, followed by open Strassman's metroplasty. Postoperatively, she still had bilateral tubal blockage despite having being hydrotubated intraoperatively using intraperitoneal spill.Conclusion: Strassman’s metroplasty is effective in the management of bicornuate uteri. However, significant challenges exist in a low-resource setting which limits its access.